The Effect of Religiosity and Product Knowledge on Trust in Islamic Banking in Purwakarta - Kusumadewi, Ade Nurhayati; Marlina, Ropi; Nugraha, Shandika Satriadi; Inomjon, Qudratov Satriadi (Islamic Research, 2024)
The purpose of this study was conducted to determine what factors influence trust in Islamic banking. In this study, two independent variables were taken, namely religiosity and product knowledge and trust as the dependent variable. The method used in this study is a quantitative with descriptive verification method with a research sample of 99 respondents. The data analysis technique used is multiple linear regression with SPSS software version 25. Based on the results of multiple linear regression analysis, this study shows that religiosity and product knowledge has a significant on the trust of Islamic banking in the city of Purwakarta. And overall independent variables have a simultaneous effect on confidence with Fcount 27.955 with a significance level of 0.000 <0.05. And the value of 0.368 R Square shows the results that all variables have an effect simultaneously as much as 36.8%. The implication of this study shows that religiosity and product knowledge variable has a direct effect on increasing the trust of Islamic banking in the city of Purwakarta. However, this study implies the need for better The importance of increasing religiosity and pay attention to product knowledge so as to increase customers to use Islamic banking services. This research is expected to provide benefits for managers of Islamic banking branch offices to increase customer trust in Islamic banking.